Istikhdām al-Taqnīyāt al-Mukhtalifah fī Ta‘līm al-Lughah al-‘Arabīyah li-al-Nāṭiqīna bi-Ghayrihā - Jamal Muhammad Sa'id Hamd (Al-Ma‘rifah, 2018)
This study aims to show the influence of using various techniques on learning Arabic by nonnative speakers.  It tries to highlight the modern techniques that suit such learning.  It also attempts to present the usefulness of such use. The significance of the study stems from the importance of teaching Arabic to nonnative speakers due to the increasing willingness to learn the language for different purposes.  The method used in this study is descriptive and analytic.  The study came out with some findings.  The major ones are: Using various techniques in teaching Arabic to nonnative speakers makes the teaching process more effective, contributes in fulfilling the educational objectives, helps in easing the process of learning, motivates learners and draws their attention.  The use of techniques also extends the learners' experience, develops their abilities and transfers them from oral learning to practical learning. Moreover, it can enable them to communicate with others.